PENGARUH PROPORSI TEPUNG JAGUNG UNGU (Zea mays var ceratina kulesh) TERHADAP KARAKTERISTIK ORGANOLEPTIK MIE KERING - Nur Asiyah; Mohammad Jusuf Randi; Nurwati Nurwati (Journal of Food Technology and Agroindustry, 2023)
Dry noodles is a food product made from wheat flour in the form of a typical noodle which has a relatively long shelf life and is easy to handle. Utilization of purple corn into flour as a processed ingredient for dry noodles can reduce imports and consumption of wheat flour, purple corn is a variety of pulut corn that contains anthocyanins as antioxidant compounds. The purpose of this study was to determine the proportion of purple corn flour on the organoleptic characteristics of dry noodles and proximate analysis of the best results of dry noodles, the method used was a factorial Completely Randomized Design (CRD) with 5 treatments and 3 replications. The treatments were J1 (90% flour: 10% purple corn flour), J2 (80% flour: 20% purple corn flour), J3 (70% flour: 30% purple corn flour), J4 (purple corn flour 60% : 40% purple corn flour), J5 (50% flour : 50% purple corn flour). The research data were analyzed using Two Way ANOVA and Duncan's further test. The results of the organoleptic test on the level of preference showed that the addition of the proportion of purple corn flour had an effect on taste and texture, but had no effect on the color and aroma of dry noodles. The best result of dry noodles was treatment J2 with the results of proximate analysis in the form of protein content (15,63%), water content (16,41%), ash content (2,34%), fat content (1,16%), and carbohydrates (64,46%).